Respuestas

2013-09-05T01:22:35+02:00
a) 2 * (3 + 5) = (2 * 3) + (2 * 5) = 16
    2 * (3 + 5) = 2 * (8) = 16 
b) 3 * (4 + 6) = (3 * 4) + (3 * 6) = 30
     3 * (4 + 6) = 3 * (10) = 30 
c)  7 * (5 + 4) = (7 * 5) + (7 * 4) = 63
     7 * (5 + 4) = 7 * (9) = 63
d) 6 * (8 + 9) = (6 * 8) + (6 * 9) = 102
     6 * (8 + 9) = 6 * (17) = 102
e) 7 * (6 + 9) = (7 * 6) + (7 * 9) = 105
    7 * (6 + 9) = 7 * (15) = 105
f)  8 * (9 + 9) = (8 * 9) + (8 * 9) = 144
    8 * (9 + 9) = 8 * (18) = 144
g) 70 * (2 + 3) = (70 * 2) + (70 * 3) = 350
     70 * (2 + 3) = 70 * (5) = 350